Chromatin modification abnormalities by CHD7 and KMT2C loss promote medulloblastoma progression - Wang, Wanchen; Kumegawa, Kohei; Chapman, Owen S.; Shiraishi, Ryo; Xiao, Zhize; Okonechnikov, Konstantin; Sun, Yang; Pfister, Stefan; Feng, Weijun; Uesaka, Naofumi; Hoshino, Mikio; Takahashi, Satoru; et al. (Cell reports, 2025)
Medulloblastoma (MB), a common malignant pediatric brain tumor arising in the cerebellum, is characterized by mutations in chromatin modifiers, highlighting the significance of chromatin modification abnormalities in its progression. While animal models have effectively demonstrated this, a comprehensive evaluation of the oncogenic potential of these mutations remains incomplete. In this study, we use CRISPR-mediated gene editing to knock out chromatin modifier genes mutated in human SHH MB, along with the Ptch1 gene, in cerebellar granule neuron progenitors of neonatal mice. This reveals that depletion of Chd7 and Kmt2c accelerates tumor growth. Multi-layered omics analysis uncovers that inhibition of the neuronal differentiation program by chromatin dysregulation is a key signaling pathway in tumor progression. Additionally, forced expression of Neurod1, a common target of these chromatin modifiers, inhibits proliferation and promotes differentiation. These findings highlight converging chromatin modification abnormalities from distinct mutations in Sonic Hedgehog MB and suggest that epigenetic drugs activating neuronal genes have significant potential as novel treatments.